THE EFFECT OF PERCEIVED VALUE ON E-COMMERCE APPLICATIONS IN FORMING CUSTOMER PURCHASE INTEREST AND ITS EFFECT ON USER LOYALTY - Berlintina Permatasari; Jaelani Jaelani (Integrated Journal of Business and Economics (IJBE), 2021)
This reserach gives special attention to the value that drives users to engage in trading activities through e-commerce. The purpose of this study is to identify the effect of perceived value on user buying interest, the effect of purchase intention on the level of trust, the effect of trust on the level of satisfaction, the effect of trust on the level of loyalty, and the effect of satisfaction on the level of loyalty. This research uses Structural Equation Modelling (SEM) analyzed by SPSS AMOS software. This study proves that perceived value is able to influence purchase intention and user trust, which in turn will form loyalty. The practical implications of this research are to provide input on the importance of perceived value to build customer loyalty, which in turn can provide sustainable benefits.